Microbiome of industrialized Minas Frescal Cheese reveals high prevalence of putative bacteria: A concern in the One Health context. (March 2021) - de Paula, A.C.L.; Medeiros, Julliane Dutra; Fernandes, G.R.; da Silva, V.L.; Diniz, Cláudio Galuppo
Abstract: The knowledge about microbiota from cheeses plays a key role in safety improvement and quality enhancement of the final product. We used a high throughput sequencing methodology to provide insights into the microbial composition of Minas Frescal Cheese (MFC). The results obtained from the analysis of 28 cheese samples showed that cheeses were brand-clustered, exhibiting unique bacterial profiles which varied in diversity and abundance of taxa. Proteobacteria dominated in all samples, corresponding to a mean of 88.7% from all sequences. Groups associated with contamination, as Pseudomonas, Acinetobacter and Vibrio were highly frequent in most of brands. Low abundance of lactic acid bacteria was also observed. The core microbiome shared by 100% of the samples indicated predominance of Enterobacteriaceae family. Our data point to a concern regarding the occurrence of potential spoilage microbiota and opportunistic pathogens in cheeses. This metataxonomic study suggests correlations between putative bacteria and antimicrobial resistance phenomenon in foodstuff, as already reported for MFC. Together these data highlight that productive chain of MFC might be related to spread of medically important bacteria, which are underestimated for their possible impact on human health. The observations may also reinforce the importance of food safety regulations facing the One Health point of view. Highlights: Microbiota of Minas Frescal Cheese was elucidated by High Throughput Sequencing. Prevalence of groups related to food contamination and low abundance of LAB. The microbiome core is enriched by Enterobacteriaceae. Opportunistic pathogens carrying antibiotic resistance gene are public health issue.